La bourgeoisie rurale dans le vignoble du Jura au xixe siècle - Borgeaud, Olivier (Annales littéraires, 2023)
The nineteenth century Bourgeoisie in the rural French Jura were not what you might expect. In sometimes delicate, sometimes down-to-earth language, they candidly discuss the running of the vineyards, the sex lives of the housemaids, their sensitivity to smells, their concerns about money or their relations with the neighbours in the farm or chateau next door. Men and women both escape from received gender roles, often far from traditional standards. Refusing to face the upheavals of the nineteenth century, they remain attached to an immutable past thus putting themselves in danger. Drawing from private correspondence, the author reveals its microhistory.